A case of choroidal metastasis in a male breast cancer - Oleksy, Piotr; Pogrzebielski, Arkadiusz; Karska-Basta, Izabella; Romanowska-Dixon, Bożena (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: We present a case of male patient under therapy due to breast cancer with choroid metastasis and exudative retinal detachment in right eye. Material and methods: A 59 years old male patient was referred with diagnosis of intraocular tumor in right eye. Three years ago radical right-side mastectomy was performed (T2N1M0). The medical history revealed that the patient was under chemoand hormontherapy due to right breast cancer with lungs, liver and mediastinum metastases. Based on the ophthalmological examination the diagnosis of intraocular tumor was established – choroidal metastasis with exudative retinal detachment. Due to tumor size and general dissemination external beam irradiation of tumor was performed. Conclusions: The majority of choroidal metastases in males are secondary to lung carcinoma, however in differential diagnosis it is necessary to consider also rare cases of breast carcinoma metastases. Treatment strategy should be considered individual depending on size, localization, presence of metastases to other organs and general condition of the patient.